PWE-093 Incidence of abnormal findings on abdominal computerised tomography and correlation with endoscopic follow-up and findings. (23rd September 2015) - Thalheimer, U; Robson, R; O'Connor, A; Borgstein, R; Wright, J
Abstract : Introduction: An increasing number of patients undergo computerised tomography (CT) of the abdomen, leading to increased demand for endoscopy. Our aim was to investigate the incidence of abnormal GI findings on abdominal CT scans in an unselected cohort of patients, the incidence of endoscopy generated and the correlation with any endoscopic findings. Methods: All abdominal CT scans performed at the North Middlesex University Hospital were evaluated from January to June 2005. CT reports were assessed for abnormalities relating to the GI tract, and endoscopy reports, histology reports and further radiology reports were reviewed. Results: A total of 1407 abdominal CT scans (1092 patients) were identified. 199 (14%) of these for 185 patients (17%), had abnormal findings relating to the GI tract. The site of the abnormality was the colon in 115, the upper GI tract in 67, small bowel in 15 patients (multiple sites in 13). Histology was available for 84 patients diagnosing malignancy in 42 (50%). 38 out of the 185 patients (20.5%) had an endoscopic procedure related to the CT findings. In 20 patients out of the 38 (53%) endoscopy confirmed the presence of an abnormality compatible with the CT findings. Malignancy was the cause in 13 of these (34%). One out of seven patients (14%) under the age of 50 had a malignant finding as compared to 12 out of 31 (39%) of patients above the age of 50. Of the 149 patients who did not undergo an endoscopic procedure, 38 had an non-endoscopic procedure or decision (eg, other imaging, surgery or biopsy). 35 had undergone an endoscopic procedure prior to CT, 35 had a known cause for the abnormality and six were known to have a significant non-GI pathology. Six patients had small bowel abnormalities and in eight a specific cause was suggested that did not require further endoscopic diagnosis. 30 patients (16%) had no endoscopy without any obvious explanation and in these a potential diagnosis could have been missed. From these findings a new pathway for endoscopy for GI abnormalities on CT has been developed. Conclusion: Abnormal findings on unselected abdominal CT scans are frequent in our practice and are compatible with abnormal endoscopic findings in half the patients investigated. Over 6 months, abnormal CT of the GI tract generated 38 new endoscopy requests with an incidence of endoscopic abnormality in half and cancer in a third. We therefore conclude that endoscopy to investigate abnormal gastrointestinal tract findings on CT scanning at the North Middlesex hospital is a necessary investigation with a high incidence of pathology encountered.